Endoscopic Repair of Cerebrospinal Fluid (CSF) Rhinorrhea with Multilayer Grafts - Manandhar, Sriti; Meghanadh, K R; Reddy, N V R (Birat Journal of Health Sciences, 2021)
Introduction: Endoscopic repair of Cerebrospinal fluid (CSF) rhinorrhea has been the most popular and the most accepted among the Otorhinolaryngologists. The advancement in the endoscopes enable surgeons to manage cerebrospinal fluid rhinorrhea adequately with good result. Objective: The aim of this study was to evaluate the outcome of endoscopic CSF rhinorrhea repair with multilayer grafts. Outcome was identified in terms of postoperative complications like infection (mainly meningitis), nasal bleeding, graft failure and CSF leak, revision surgery. Methodology: A retrospective prospective study was conducted in 21 patients who had undergone endoscopic CSF rhinorrhea repair with use of multilayer grafts in a period of January 2016 to December 2018 in Department of ENT and Head and Neck Surgery in MAA ENT HOSPITAL, HYDERABAD, INDIA. All the patients were diagnosed according to history, clinical examination, diagnostic nasal endoscopy, CSF fluid analysis and radiological investigation. The materials used for the repair of CSF rhinorrhea were surgicel, temporalis fascia, conchal chondroperichrondrium, middle turbinate free mucoperiosteum graft, thigh fat and fascia lata. The follow up period of patients range from 14-44 months. The outcome of endoscopic CSF repair with use of multilayer grafts was evaluated by electronic records regarding recurrence of CSF rhinorrhea post-surgery, hospital admission, revision surgery and digital record of rigid endoscopic findings for the status of graft uptake and CSF leak. Results: In all patients, CSF leak was successfully repaired with use of multilayer grafts in first attempt without any complication. There was female predominance with male to female ratio of 1:6.The mean age of presentation was 43.09years. All 21 patients were presented with spontaneous CSF leak with unknown cause. In 21 patients only one patient presented with bilateral cerebrospinal fluid leak. Cribri form plate was the commonest site of defect in which defect medial to middle turbinate was the commonest followed by ethmoid roof and lateral wall of sphenoid. None of the patients developed meningitis after surgery. None of the patients required lumbar drain. None of the patients presented with cerebrospinal fluid rhinorrhea postoperatively. Conclusions: Endoscopic repair of Cerebrospinal fluid rhinorrhea with the use of multilayer grafts is the safer and effective method with good outcome.